Fast integral terminal sliding mode control with a novel disturbance observer based on iterative learning for speed control of PMSM. (March 2023) - Yang, Tian; Deng, Yongting; Li, Hongwen; Sun, Zheng; Cao, Haiyang; Wei, Zongen
Abstract: This study revolves about the speed control of a permanent magnet synchronous motor (PMSM) with torque ripple and external disturbance. To enhance the performance of the PMSM speed control in response, robustness and torque ripple suppression, a hybrid control technique is presented by combining a novel disturbance observer based on iterative learning strategy (ILC-DOB) and a fast integral terminal sliding mode control (FITSMC) method. Firstly, an iterative learning law is used to enhance the conventional high-gain disturbance observer (DOB) to improve the estimation performance for periodic disturbance. Then, a new fast integral terminal sliding mode surface is proposed to increase the tracking error convergent speed of the traditional integral terminal sliding mode control (ITSMC) when the speed error is distant from the equilibrium point. Finally, the estimated total disturbance is incorporated as a feed-forward compensation to the enhanced FITSMC. According to experimental results, the presented method can ensure better speed-tracking performance and significant disturbance rejection capability of the PMSM drive system. Highlights: This paper proposes a control strategy for the PMSM drives by combining the fast integral terminal sliding mode controller (FITSMC) and a novel disturbance observer based on iterative learning strategy (ILC-DOB). The FITSMC is proposed to improve the tracking error convergent speed of the traditional integral terminal sliding mode control when the speed error is distant from the equilibrium point. The ILCDOB is designed to estimate the periodic disturbance and add a corresponding feed-forward compensation item to the FITSMC. The effectiveness of the proposed method is verified by experimental results.